2010
DOI: 10.3109/07420520903398567
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Illumination Dimmer Than Starlight Altered the Circadian Rhythm of Adult Locomotor Activity of a Fruit Fly

Abstract: The effects of nocturnal irradiance tenfold dimmer than starlight intensity on the locomotor activity rhythm of Drosophila jambulina were investigated in two types of light-dark (12 h:12 h) cycles, in which light intensity of the photophase was 10 lux while that of the scotophase was either 0 lux for control flies or 0.0006 lux for experimental flies. Activity onset in the experimental flies was approximately 5.4 h prior to lights-on, so it occurred around midnight. However, activity onset of the control flies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…For example, bright nocturnal irradiance adversely affected several aspects of the circadian physiology and behavior of humans (Kloog et al, 2011;Siegelova et al, 2006) and social voles, Microtus socialis (Zubidat et al, 2007). Similarly, dim nocturnal irradiance varying from starlight to moonlight intensity modified many features of the circadian locomotor activity rhythm of bats (Erkert et al, 1976;Joshi & Chandrashekaran, 1982;Vanlalnghaka et al, 2006), hamsters (Evans et al, 2005;Gorman & Elliot, 2004;Gorman et al, 2003Gorman et al, , 2006, and fruit fly, Drosophila (Bachleitner et al, 2007;Hirsh et al, 2010;Kempinger et al, 2009;Thakurdas et al, 2009Thakurdas et al, , 2010. Thus, several studies have reported the effects of the intensity of nocturnal illumination on the circadian rhythms of animals.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, bright nocturnal irradiance adversely affected several aspects of the circadian physiology and behavior of humans (Kloog et al, 2011;Siegelova et al, 2006) and social voles, Microtus socialis (Zubidat et al, 2007). Similarly, dim nocturnal irradiance varying from starlight to moonlight intensity modified many features of the circadian locomotor activity rhythm of bats (Erkert et al, 1976;Joshi & Chandrashekaran, 1982;Vanlalnghaka et al, 2006), hamsters (Evans et al, 2005;Gorman & Elliot, 2004;Gorman et al, 2003Gorman et al, , 2006, and fruit fly, Drosophila (Bachleitner et al, 2007;Hirsh et al, 2010;Kempinger et al, 2009;Thakurdas et al, 2009Thakurdas et al, , 2010. Thus, several studies have reported the effects of the intensity of nocturnal illumination on the circadian rhythms of animals.…”
Section: Introductionmentioning
confidence: 94%
“…Besides, the detection of the extremely dim scotophases used in the present experiments is not a herculean task for this strain of D. jambulina. This is because it is already endowed with exceptionally diminished circadian photic threshold for entrainment by virtue of its adaptation to the dim natural photic ambience at its breeding site in the Sapota orchard (Thakurdas et al, 2010).…”
Section: Or S Duration (H)mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the dim natural and artificial nighttime illuminations altered the attributes of entrainment and free-running rhythm of the pupal eclosion of D. jambulina 14 . In the same species, the nocturnal illumination at 0.0006 lx advanced the activity onset by several hours, extended the activity duration, enhanced the activity level and shortened the period of free-running rhythm 15 . Varying durations (9–15 h) of the dim scotophase at 0.0006 lx modulated the fundamental properties of the circadian pacemakers that controlled the adult locomotor activity rhythm of D. jambulina 2 .…”
Section: Introductionmentioning
confidence: 99%